2011
DOI: 10.2215/cjn.09091010
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of the 3-Hydroxy-3-methylglutaryl-CoA Reductase Inhibitors in Chronic Kidney Disease, Dialysis, and Transplant Patients

Abstract: SummaryCoronary heart disease (CHD) is the leading cause of death in Western civilizations, in particular in chronic kidney disease (CKD) patients. Serum total cholesterol and LDL have been linked to the development of atherosclerosis and progression to CHD in the general population. However, the reductions of total and LDL cholesterol in the dialysis population have not demonstrated the ability to reduce the morbidity, mortality, and cost burden associated with CHD. The patients at greatest risk include those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…This result suggested that vitamin E-bonded dialyzer therapy might not be efficacious for controlling the HD-induced atherosclerosis and dyslipidemia, particularly when compared with other approved lipid-lowering drugs. 42 Several important potential study limitations to this systematic review should be acknowledged. Firstly, mostly included studies were of low quality and small-size, only two studies explained the randomization method, and most of studies were not blinded designed.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that vitamin E-bonded dialyzer therapy might not be efficacious for controlling the HD-induced atherosclerosis and dyslipidemia, particularly when compared with other approved lipid-lowering drugs. 42 Several important potential study limitations to this systematic review should be acknowledged. Firstly, mostly included studies were of low quality and small-size, only two studies explained the randomization method, and most of studies were not blinded designed.…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been shown to decrease the mortality and CVD events in people with early stages of CKD, but have little or no effect on the HD population, and have uncertain effects in kidney transplant recipients (23). The detailed relationships among the plasma cholesterol level, cholesterol reduction, the use of statins, and the reduction of CVD have not been proven in the HD population (24). Thus, although fibrates and statins are not indicated for HD patients without hyperlipidemia, EPA or DHA supplementation may be suitable for treating milder disorders of lipid metabolism because of their rare induction of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…10 Older individuals with CKD have a reduced life expectancy, high competing risk for other CKD-related outcomes, and a higher risk for statin-related adverse events and drug-drug interactions. [23][24][25] These factors can reduce the potential benefit of statin initiation among the very old with CKD. Given the high prevalence of CKD among individuals $80 years of age, 26 studies are needed to identify the benefits of statins for this high-risk group.…”
Section: Discussionmentioning
confidence: 99%